Rapid Alert System for Food and Feed reports as a source of information on food hazards - Mikulec, Anna; Zborowski, Marek; Kowalski, Stanisław (Journal of Education, Health and Sport, 2023)
Introduction Food safety is a major challenge worldwide and an important factor frequently taken into account by consumers when making food choices. Over the years, a number of unfavorable phenomena related to food adulteration and an increase in its contamination have been observed, which in turn translates into a lower level of food quality and safety and a decrease in consumer confidence. Aim The aim of this study was to analyze the Rapid Alert System for Food and Feed (RASFF) reports from 2019-2021 in terms of types of hazards in food. Materials and methods The research material consisted of the annual reports of the RASFF for the years 2019-2021. Results The submissions to the RASFF per product type system were dominated by those related to food. In 2020 and 2021, the most notifications concerned fruits and vegetables, dietetic food, food supplements, and fortified foods. In the group of 10 products causing the most frequent notifications, there are products of animal origin: meat and meat products (other than poultry), fish and fish products, milk and milk products, poultry meat and poultry meat products. The main threats associated with food in the last three years were contamination with Salmonella in poultry meat and poultry meat products, herbs and spices, and nuts, nut products and seeds; aflatoxins, especially in nuts, nut products and seeds; and pesticide residues in fruit and vegetables. Conclusion The observed increase in the number of notifications in the RASFF reports in 2019-2021 shows that all EU Member States are involved in monitoring food safety risks. The functioning of the RASFF system enables immediate action to be taken in the EU countries in relation to the risk, and allows for quick information transfer and elimination of products that are hazardous to the health of the consumer.